"Neuropsychology for you" - Weiler-Wichtl, Liesa J.; Fohn-Erhold, Verena; Klein, Alina; Fries, Jonathan; Schneider, Carina; Holzer, Angelika Elisabeth; Schreiber-Gollwitzer, Beate; Lüttich, Peggy; Ross, Henning; Pletschko, Thomas; Hansl, Rita; Hopfgartner, Maximilian; et al. (Zeitschrift für Neuropsychologie, 2023)
My Logbook" is a method to translate evidence-based guidelines for psychosocial care in pediatric neurooncology into practice. One part of "My Logbook" is the standardized instrument "Neuropsychology for You," developed by an interdisciplinary expert team. It consists of two booklets that include creative and challenging methods to support the implementation of basic standards into practice. The booklet "1, 2, 3 - All About Neuropsychology" focuses on neuropsychological therapy, while "Look Carefully - Psychosocial Assessment" addresses psychosocial assessment. Both booklets explain the topics in a patient-oriented and age-appropriate way and motivate patients to actively participate in two sessions each (psychoeducational, work and exercise, and reflection). The evaluation of the booklets showed a positive association between neuropsychological assessment and therapy. Furthermore, the patients' positive emotions and the subjective level of information increased. Therefore, "Neuropsychology for You" is a promising tool for the practical and low-threshold implementation of neuropsychological assessment and therapy into clinical practice.